Accountability for quality of care: Monitoring all aspects of quality across a framework adapted for action. Issue 1 (7th December 2015) - Hulton, Louise; Matthews, Zoë; Bandali, Sarah; Izge, Abubakar; Daroda, Ramatu; Stones, William
Abstract: Quality of care is essential to maternal and newborn survival. The multidimensional nature of quality of care means that frameworks are useful for capturing it. The present paper proposes an adaptation to a widely used quality of care framework for maternity services. The framework subdivides quality into two inter‐related dimensions—provision and experience of care—but suggests adaptations to reflect changes in the concept of quality over the past 15 years. The application of the updated framework is presented in a case study, which uses it to measure and inform quality improvements in northern Nigeria across the reproductive, maternal, newborn, and child health continuum of care. Data from 231 sampled basic and comprehensive emergency obstetric and newborn care (BEmONC and CEmONC) facilities in six northern Nigerian states showed that only 35%–47% of facilities met minimum quality standards in infrastructure. Standards for human resources performed better with 49%–73% reaching minimum standards. A framework like this could form the basis for a certification scheme. Certification offers a practical and concrete opportunity to drive quality standards up and reward good performance. It also offers a mechanism to strengthen accountability.